MARKETING STRATEGY OF MORIFLOUR MORINGA POWDER (CASE STUDY: PT. KELORIA MORINGA JAYA) - Pratiwi, Henny; Lubis, Yusnidar; Riyadh, Mhd. Ilham (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Increasing competition in the herbal product industry requires firms to adopt effective and sustainable marketing strategies. Moringa-based products have significant market potential; however, their development is often constrained by internal limitations and external pressures. This study aims to analyze the internal and external marketing conditions of MoriFlour Moringa Powder at PT. Keloria Moringa Jaya and to formulate appropriate marketing strategies. A qualitative descriptive approach with a case study design was employed. Data were collected through interviews, observations, documentation, and questionnaires, and analyzed using SWOT analysis through IFAS and EFAS matrices. The results indicate that the total IFAS score was 0.98 and the EFAS score was 0.93, demonstrating the dominance of strengths and opportunities over weaknesses and threats. The SWOT diagram places the company in Quadrant I, indicating a favorable strategic position. Accordingly, growth-oriented strategies such as market penetration and market development are recommended by leveraging product quality and expanding herbal market opportunities. These findings confirm that SWOT analysis is an effective tool for formulating marketing strategies in functional plant-based agro-industries.